Jean Libis, Fabio Ferreira, Catherine Gublin, Sarah Mezaguer (eds.), Les Lectures de Gaston Bachelard. Index bibliographique (Altre Modernità, 2012)
Jean Libis, Fabio Ferreira, Catherine Gublin, Sarah Mezaguer (eds.), Les Lectures de Gaston Bachelard. Index bibliographique (Paris, Presse Universitaire de Franche-Comté, 2011 ISBN: 978-2-84867-392) di  Aurosa Alison